Evaluation of the applied accounting by the sufficiency economy concept Salaya sub-district, Phuttamonthon district Nakorn-Phatom - Injun, Supanee (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objectives of this research were (1) study the participant’s opinion toward applied accounting project by the sufficiency economy concept of the community development volunteer leaders and network, Salaya sub-district, Phuttamonthon district Nakorn-Phatom and (2) the suggestions of the applied accounting project by the sufficiency economy concept. The data were collected by the quantitative method which the research population were community development volunteer leaders and network, Salaya sub-district, Phuttamonthon district Nakorn-Phatom, 163 subjects and statistics used were frequency percentage mean and standard deviation. The research results may be concluded that the project evaluation in overall was found in high level (mean = 3.77). The aspect with the highest mean value was the knowledge aspect, next was the place and service aspect and the least aspect was the documentary aspect. The participant’s suggestions were the project should be operating continuously for continuous development and should measure the participant’s knowledge before and after participating the project. Article history : Received 29 July 2018 Revised 11 February 2019 Accepted 22 February 2019 SIMILARITY INDEX = 1.81